Synthesis and Characterization of Tetracycline Loaded Methionine-Coated NiFe2O4 Nanoparticles for Anticancer and Antibacterial Applications - Faten Eshrati Yeganeh; Amir Eshrati Yeganeh; Bahareh Farasati Far; Afsoun Mansouri; Belay Zeleke Sibuh; Saravanan Krishnan; Soumya Pandit; Walaa F. Alsanie; Vijay Kumar Thakur; Piyush Kumar Gupta (Nanomaterials, 2022)
In the present study, nickel ferrite (NiFe2O4)-based smart magnetic nanoparticles were fabricated and coated with methionine. Physiochemical characterization of the obtained Met-NiFe2O4 nanoparticles revealed the presence of methionine coating over the nanoparticle surface. Drug release study indicated that Tet-Met-NiFe2O4 nanoparticles possess pH-responsive controlled drug release behavior for tetracycline (Tet). The drug loading content for Tet was found to be 0.27 mg/L of nanoparticles. In vitro cytotoxicity test showed that the Met-NiFe2O4 nanoparticles is biocompatible. Moreover, this magnetic nanostructured material shown strong anticancer property as these nanomaterials significantly reduced the viability of A375 cells when compared to free Tet solution. In addition, Tet-Met-NiFe2O4 nanoparticles also showed strong antibacterial activity against different bacterial pathogens.